El trabajo con gomas en el desarrollo de la resistencia a láctica y la potencia máxima a láctica, en los nadadores de la categoría juvenil. - Ponce, Herman (2011)
This work focuses on work study with rubbers in developing Resistencia Aláctica and Potencia Máxima Aláctica in swimmers Club SIRUIS of town Riobamba our theme was chosen by importance must have utilization rubber in training sportsmanship, same will assist coaches preparation and performance swimmer, provisionally This investigative work structured in six chapters where is established problem statement. The most notorious not perform proper training rubber develop Resistencia Aláctica and Potencia Máxima Aláctica in swimmers youth category. Framework Theoretical served to investigate three variables were development Resistencia Aláctica is capacity withstand Efforts which its short duration not results lactate accumulation maximum, Potencia Máxima Aláctica is obtaining maximum energy unit time working with goma is material sporting versatile help development physical qualities whether in Sports elite or aficionados. Framework Methodological helps us specify method here would deductive inductive used for developing this work investigative design would field because develop in scene, supported instruments like were Observation Guide and Survey where perform tabulating results.